"Unexpected event": Having an infants with cleft lip and/or palate. (5th November 2020) - Çınar, Sevil; Ay, Ayşe; Boztepe, Handan; Gürlen, Eda
Abstract: This study aimed to determine the difficulties that the mothers of infants with a cleft lip and/or palate (CL/P) go through, the problems they encounter in this process, and how they perceive the support of healthcare professionals, families, and friends. The study used a phenomenological approach from qualitative research methods. The study sample included 18 mothers of 0 to 3‐month‐old infants with CL/P. The data were collected using socio‐demographic information form and semi‐structured interview form. The data obtained from the interviews were evaluated using content and thematic analysis approaches. On the basis of the interviews conducted with mothers of infants with CL/P, the following themes emerged: (a) "unexpected event: having an infant with CL/P, " (b) "using social media, " (c) "stigma, " and (d) "uncertainty of long‐term treatment." In this study, it was determined that mothers experienced shock, confusion, sadness, and disappointment in this process; therefore, they used social media to seek support from the families as well as conducted research on the disease that involved a lot of uncertainty due to long‐term treatments. The present study can help healthcare professionals, who play a role in the care and treatment of infants with CL/P, to understand and know what mothers need in the preoperative period.